2022
DOI: 10.1111/ctr.14616
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenicity‐2 (ST2) is a promising biomarker in heart transplantation

Abstract: Background To evaluate the association between donors’ and recipients’ serum levels of soluble ST2 (sST2) and recipients’ outcome after heart transplantation (HT). Methods Blood samples were collected in 50 heart donors before organ procurement and in 50 recipients before HT (D0), a week after HT (D7) and at every first year's endomyocardial biopsy (EMB); sST2 levels were evaluated by ELISA. Results Donors who sustained a cardiac arrest, had significantly higher sST2 levels. Recipients on national high emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Several biomarkers have been proposed to detect and monitor allograft rejection after HT. The ST2/IL-33 pathway has been shown to be involved in the context of acute rejection after HT in both adults and pediatric heart recipients [36,37]. Serum sST2 levels significantly rise in the context of acute rejection showing a linear association with severity of acute rejection and decline after successful rejection therapy [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers have been proposed to detect and monitor allograft rejection after HT. The ST2/IL-33 pathway has been shown to be involved in the context of acute rejection after HT in both adults and pediatric heart recipients [36,37]. Serum sST2 levels significantly rise in the context of acute rejection showing a linear association with severity of acute rejection and decline after successful rejection therapy [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study explored the role of sST2 serum levels in heart donors and allograft function following heart transplantation for the first time [ 75 ]. The authors demonstrated that brain-dead organ donors have considerably high levels of sST2.…”
Section: St2 Involvement In Cardiovascular Diseasesmentioning
confidence: 99%
“…The higher levels were observed in older donors and in donors with reduced LVEF, or have need for inotropic support and after-cardiac-arrest resuscitation. Additionally, elevated sST2 serum levels in donors were associated with allograft dysfunction in heart recipients [ 75 ]. Assessment of biomarkers is of paramount importance in potential heart donors as it may provide important predictive information and allows for risk stratification, especially in marginal donors, who are increasingly accepted due to the for scarcity of heart donors [ 76 ].…”
Section: St2 Involvement In Cardiovascular Diseasesmentioning
confidence: 99%